Multiple grain-size fraction analysis of heavy minerals and the provenance identification of sediments from the abandoned Huanghe River, eastern China - Wang, Mengyao; Jin, Bingfu; Jia, Jianjun (Journal of oceanology and limnology, 2023)
The quantitative analysis of sediment sources in a sink is an important scientific topic and challenge in provenance research. The characteristics of heavy minerals, combined with the geochemical constituents of detrital grains, provide a reliable provenance-tracing approach. We developed a mineral identification method to analyze the multiple grain-size fraction of sediments, from which the elemental geochemistry of hornblende was used to compare the characteristics of sediments from the Huaihe River and Huanghe (Yellow) River in eastern China. Elements that were statistically identified as being able to discriminate sediment provenance were employed to perform a quantitative analysis of the sources of sediments of the abandoned Huanghe River. Results reveal that the Huaihe River is characterized by a high amphibole content of >60% and that the Huanghe and abandoned Huanghe rivers have greater abundances of limonite and carbonate minerals compared with those of the Huaihe River. The contents of trace elements and rare earth elements in hornblende show that the sediments of the abandoned Huanghe River are similar to those of the Huanghe River but different from those of the Huaihe River. Furthermore, chemical mass balance was used to calculate the relative contributions of different provenances of sediment from the abandoned Huanghe River, and nine trace elements of hornblende were identified as discriminators of provenance. Approximately 2% of the hornblende in the abandoned Huanghe River is derived from the Huaihe River and 98% from the Huanghe River. Considering the proportion of hornblende in the total sediment, it is inferred that the contribution of Huaihe River sediment to the abandoned Huanghe River is approximately 0.5%. This study shows that mineral analysis using multiple grain-size fractions (within the wide range of 1Φ to 6Φ) with assessment in elemental geochemistry of hornblende can characterize the provenance of fluvial material in coastal zones.